The issue in the appointment of female leaders and appointment of a non-muslim leader / Muhammad Irfan Imaduddin Azran … [et al.] - Azran, Muhammad Irfan Imaduddin; Ramli, Muhammad Adi Irfan; Sallehudin, Sadiq Najwan; Zuhairi, Muhammad Amir Iqbal; Hamzah, Amirul Khalis (2023)
Leadership in Islam is deeply rooted in the principles of justice, compassion, and servitude. The Islamic concept of leadership goes beyond mere authority; it encompasses a profound sense of responsibility and accountability. In the Islamic tradition, leadership is viewed as a sacred trust bestowed upon individuals, requiring them to uphold the values of integrity, fairness, and humility.